Reconstruction of Bonds Arrangements in Indonesian Capital Market Justice-Based Value - elvira fitriyani pakpahan (UNISSULA, 2017)
Trustee contracts referring to the special provisions on guarantees stipulated by Bapepam (Capital Market Supervisory Agency)/OJK (Financial Service Authority) as referred in item 4 letter E Kep. Bapepam-LK No.412 / BL / 2010 are considered too general. The provision of guarantee on number 4 letter E Kep. Bapepam No.412 is limited to informational provisions, not a requirement. The purpose of this paper is to know and analyze the implementation of bond arrangements and weaknesses in the capital market of Indonesia based on the value of justice. Why there are weaknesses in the implementation of bond arrangement in Indonesia capital market. This research used sociological juridical method. The theories used to analyze were the theory of Degrading Justice as the Grand Theory, Theory of Legal Protection as the Middle Range Theory and Theory of the Covenant as Applied Theory. Based on the results of research implementation of bond arrangement in Indonesia capital market does not give justice value to the parties such as issuer, trustee and investor in particular. Unclear arrangements in Bapepam-LK's Decree on General Provisions and Trustee Contracts under the Warranty (if any) do not provide legal certainty and fairness to bond investors in the event of default. The weaknesses in the implementation of bonds arrangement in the Indonesian capital market due to the functions and duties of the Trustee listed in UUPM have no regulatory arrangements, as well as the absence of guidelines/standards in the preparation of the trustee contract. The reconstruction of the law shall be conducted by changing the special provisions of Bapepam Decree Number 412 on item 4 letter E concerning the guarantee (if any) by removing / removing the existing word in parentheses (if any), as it does not reflect the value of legal certainty and dignified justice.